Perbandingan Insidensi Nyeri Tenggorok Pada Penggunaan Jeli Lidokain 2% Dibandingkan Jeli aqua Pasca Anestesi Umum Dengan Pipa Endotrakea - , dr. Shila Suryani, Dr. dr. Sri Rahardjo, SpAn.KNA.NCC ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Sore throat is a common problem in first 24 hours postoperative periode following the use of endotracheal intubation during general anesthesia. It was postulated that this effect is because of irritation, inflamation, and even ischaemia of the airway. Lidocaine is a local anesthetic drug which commonly used when intubation is needed. One of the benefit of lidocaine is to reduced sore throat. The aim of this study is to compare sore throat incidence between the application of 2 % lidocain gel and aqua gel on the tracheal tubeâs cuff in general anesthesia. Method. This Randomized Controlled Trial research has been performed in 94 male or female patients, 18- 50 years old, ASA I or II , no difficult intubation predictions and Body Mass Index (BMI) less than 30 kg/m2 who underwent elective surgery under general anesthesia. Patient is randomized into 2 groups. Group A was given lidocaine jelly on tracheal tube cuff and group B was given aqua jelly. Sore throat and its severity degree was assessed 1 hour and 24 hours postekstubation. Result and conclusion. 94 sample of this study was obtained 45 samples group A, 44 samples group B, and 5 samples drop out. Incidence of sore throat one hour postextubation is 17,78% for group A and 31,82% for group B. Incidence of sore throat 24 hours postextubation is 11,11% for group A and 25% for group B. However, this defference was not statistically significant (p > 0,05). This research shows that there are difference incidence of sore throat between lidocaine jelly and aqua jelly whereas incidence of sore throat lidocaine jelly is lower than aqua jelly.